(untitled) (Prilozi za orijentalnu filologiju, 2017)
A quest of ”treasure” from the Lord’s treasury hidden in the most delicate depths of human being is a leit motif we will often come across in the works by Persian sufi poets. A story from Mesnevi, a widely known sufi poetic work by Jalal Ad-Din Rumi treating the said motif, served as a framework for Paul Coelho’s novel ”Alchemist” earning him worldwide fame. The text aspires to encourage the reader to try to discover, through his mystic experience of encounter with his own light self (man-e rūhānī), the meaning of the ”spiritual alchemy” which is, indeed, the alchemy of eternal bliss.